Factors Affecting Motivation and Retention of Village Health Workers and Recommended Strategies: a systematic review from 11 developing countries - Dolley Tshering; Phudit Tejativaddhana; David Briggs; Neyzang Wangmo (ACHSM, 2018)
Introduction: Motivation and retention of village health workers (VHWs) are crucial for the continuity, sustainability, and success of health programs. VHWs are the first point of contact for rural communities, providing health services to improve access and health coverage which, for a variety of logistical reasons, cannot be reached by the district health care system. Thus VHWs are critical for ultimately ensuring universal health coverage. However, systematic review revealed that there are numerous factors that affects their motivation and retention, leading to high dropout rates and hampering the delivery of health services to the community. This review intends to examine contextual factors affecting motivation and retention of VHWs in their roles and identify recommendations and strategies to motivate and retain them in the systems. Method: Five electronic databases and two search engines were accessed. Nineteen studies met the inclusion criteria for the final review. An in-depth reading of all the articles was undertaken to gather and compile the relevant themes. Content analysis was done based on the list of specific categories that are relevant to motivation and retention.  Result: Findings from the systematic review revealed different levels of factor affecting motivation and retention of village health workers. It was finally contextualized and categorized into four main domains such as individual, family, social or community and organizational or systems levels. Financial incentives under the organizational factors was highlighted for the demotivation and the discontentment for the VHWs. Conclusion: Financial factors under the organization were often key in the studies reviewed. However, there were also many other factors, sometimes surprising or unintuitive, influencing the motivation and retention of village health workers.